Pengkajian Penggunaan Media dalam Pembelajaran Bahasa Arab oleh Mahasiswa Pendidikan Bahasa Arab 2023 - Marsaa Setiana; Rayya Raihana; Rusyda Ainun Sajidah; Umar Abdul Aziz; Ahmad Fu’adi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Learners, in this case language learners, often experience difficulties in learning. This difficulty can be seen from many things. Due to the various difficulties experienced by Arabic language learners, a strategy is needed in understanding students so that Arabic language learning can be received in an effective and efficient way, so that learning can be carried out enthusiastically by students. Researchers want to examine the influence of visual media on Arabic language learning. By conducting research on the influence of media in learning, teachers can use appropriate strategies for their students. The type of research used in this article is descriptive analysis with quantitative methods. The respondents in this research were 27 active students at the Indonesian University of Education, Arabic Language Education study program. In this research it can be seen that most students as respondents use visual media as their strategy in learning Arabic. They also feel the benefits of the media they use in learning. Visual media is a good strategy for students to learn something, in this case learning Arabic. So that teachers can use visual media in learning Arabic. Apart from teachers, students can also use this visual media to study independently.